Stiffness Evaluation of Basalt Aggregates as Replacement Aggregates in Hot Mix Asphalt (HMA) Mixtures - Harun, Zaid; Mohd Nasir, Nur Athirah; Ruhaizat, Nurul Dianah; Bujang, Hazirah (Multidisciplinary Applied Research and Innovation, 2024)
Pavement deformation is a common problem in flexible pavements in Malaysia due to poor material quality and quantity. To address this issue, basalt aggregates are being used as replacement aggregates in Hot Mix Asphalt (HMA) mixtures. The study aims to analyze the characteristics and variability of basalt aggregates and asphalt binder materials, as well as evaluate the volumetric parameters of HMA using basalt aggregate. Additionally, a marshall stability test will be conducted to analyze the performance of the mix design using basalt aggregate. Based on the average percentage in review studies, the basalt aggregate employed in this study is 0, 25, 50, 75, and 100% by weight of total aggregate. The study would be carried out to assess the stiffness of asphalt mixtures using basalt aggregate at higher mix temperatures. The aggregate that would be used in this study were granite and basalt and asphalt binder grade 60/70 as a bonding agent. To mix the material, a marshall mix design would be used in this study. Then, a marshall stability test would be conducted to analyzed the performance of the mix design using basalt aggregate. Based on result of Marshall test, the stiffness value for optimal basalt aggregate mixture was obtained at 25% which is 80.376 kN/mm, while the control sample stiffness value is 77.941 kN/mm. The compressive test shown that all the samples are followed the JKR specification for stiffness which is more than 2.6 kN/mm. This experiment indicates that a mixture of asphalt and basalt aggregate replacement fulfilled the requirements and can still be emplyed for improving the pavement.